The value and implementation of routine ophthalmic examination in the era of HAART. (January 2021) - Li, Wangting; Wang, Xiaoli; Zhao, Lanqin; Lin, Duoru; Yang, Yahan; Liu, Zhenzhen; Wu, Xiaohang; Wang, Jinghui; Zhu, Yi; Chen, Chuan; Zhang, Xiayin; Wang, Ruixin; et al.
Abstract: Background: The high prevalence of ocular manifestations (OMs) in patients with human immunodeficiency virus (HIV) infection and chronic diseases such as diabetes has become a global health issue. However, there is still a lack of an appropriate ophthalmic diagnostic procedure for the early detection of OMs in this population, leading to the risk of an irreversible visual impairment that substantially affects the quality of life of these patients. Methods: The Guangzhou HIV Infection Study was a retrospective study that enrolled hospitalised HIV-infected patients in Guangzhou between January 2005 and December 2016, period corresponding to the highly active antiretroviral therapy (HAART) era in China. We collected data on OMs, systemic diseases, hospitalisation, and demographic characteristics. We classified the patients into 3 groups according to the ophthalmic examination mode they underwent: the non-ophthalmologist examination group (patients hospitalised in 2005–2011 who were only treated by infectious disease physicians), the on-demand ophthalmic examination group (patients hospitalised in 2012–2013 who were referred for a consultation with an ophthalmologist), and the routine ophthalmic examination group (patients hospitalised in 2014–2016 who routinely underwent standard ophthalmic examinations). Binary logistic regression models were used to investigate the factors related to OMs. Findings: A total of 8, 743 hospitalised HIV-infected patients were enrolled. The prevalence of detected OMs were 1.5% in the non-ophthalmologist examination group, 1.9% in the on-demand ophthalmic examination group, and 12.8% in the routine ophthalmic examination group. The odds of detection of OMs were highest in the routine ophthalmic examination group (adjusted odds ratio [aOR]=9.24, [95%CI, 6.51–13.12], compared to the non-ophthalmologist examination group). The detection of all types of OMs increased substantially, with keratitis, retinitis and vascular abnormalities increased the most (by 15.8–20.0 times). In the routine examination group, patients who were older than 50 years, males, with medical insurance, and were not resident in Guangzhou, had higher odds to have OMs. Several systemic diseases also increased the odds of OMs, with the highest odds among patients with a cytomegalovirus infection (aOR=5.59, [95%CI, 4.12–7.59]). Patients with retinitis, retinopathy and conjunctivitis had higher odds of having a CD4 + T cell counts less than 200 cells/μL compared to the patients that did not have these referred OMs. Interpretation: The implementation of a routine ophthalmic examination has improved the odds of OM detection by approximately 9 times and increased the diagnosis rates of all types of OMs. Therefore, we encourage all HIV-infected patients to undergo regular ophthalmic examinations. Patients with OMs, especially retinopathy and retinitis, need to be evaluated for immune function (such as CD4 + T cell counts) and systemic diseases.